Diagram Kendali Triple Homogeneously Weighted Moving Average dan Penerapannya pada Proses Plating Aksesori Mobil PT. XYZ - Fairuza Amanda Belia; Suliadi Suliadi (UNISBA Press, 2023)
Abstract. Quality control is carried out to maintain or improve product quality to meet consumer satisfaction. One of the methods that can be used is control chart. Triple Homogeneously Weighted Moving Average (THWMA) is one of the control chart techniques that can be used in quality control. The Triple Homogeneosly Weighted Moving Average control chart is a control chart for efficient monitoring of the process average under zero state and steady state which is very sensitive in identifying small and continuous changes in the process effectively and using three times sample information. THWMA control is considered superior to the previously existing Homogeneosly Weighted Moving Average (HWMA) and Double Homogeneosly Weighted Moving Average (DHWMA) control charts and from other competitors. In our thesis we will apply a THWMA control chart to monitor the plating process of PT. XYZ. The results obtained in Phase I of the in control chart, so that the parameter values ​​used in Phase II are of 10.691 dan of 0.67. Phase II control chart using K = 2.994 and λ = 0.25, it is found that the THWMA control chart is controlled. Abstract. Quality control is carried out to maintain or improve product quality to meet consumer satisfaction. One of the methods that can be used is control chart. Triple Homogeneously Weighted Moving Average (THWMA) is one of the control chart techniques that can be used in quality control. The Triple Homogeneosly Weighted Moving Average control chart is a control chart for efficient monitoring of the process average under zero state and steady state which is very sensitive in identifying small and continuous changes in the process effectively and using three times sample information. THWMA control is considered superior to the previously existing Homogeneosly Weighted Moving Average (HWMA) and Double Homogeneosly Weighted Moving Average (DHWMA) control charts and from other competitors. In our thesis we will apply a THWMA control chart to monitor the plating process of PT. XYZ. The results obtained in Phase I of the in control chart, so that the parameter values ​​used in Phase II are of 10.691 dan of 0.67. Phase II control chart using K = 2.994 and λ = 0.25, it is found that the THWMA control chart is controlled.